2017
DOI: 10.3389/fnagi.2017.00283
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Decline in Anticipatory Motor Planning and Its Relation to Cognitive and Motor Skill Proficiency

Abstract: Anticipatory motor planning abilities mature as children grow older, develop throughout childhood and are likely to be stable till the late sixties. In the seventh decade of life, motor planning performance dramatically declines, with anticipatory motor planning abilities falling to levels of those exhibited by children. At present, the processes enabling successful anticipatory motor planning in general, as do the cognitive processes mediating these age-related changes, remain elusive. Thus, the aim of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 79 publications
10
58
0
1
Order By: Relevance
“…The present results add to the existing literature suggesting that motor planning is modified with aging (Kanekar and Aruin 2014;Kubicki et al 2016;Casamento-Moran et al 2017;Wunsch et al 2017;Stöckel et al 2017). Neuroscientists have first interpreted motor planning modifications as a deterioration of feedforward processes (proactive strategies) that urges older adults to favor feedback processes (reactive strategies).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The present results add to the existing literature suggesting that motor planning is modified with aging (Kanekar and Aruin 2014;Kubicki et al 2016;Casamento-Moran et al 2017;Wunsch et al 2017;Stöckel et al 2017). Neuroscientists have first interpreted motor planning modifications as a deterioration of feedforward processes (proactive strategies) that urges older adults to favor feedback processes (reactive strategies).…”
Section: Discussionsupporting
confidence: 71%
“…For example, previous studies have shown that motor planning adapts reaching trajectories to changing inertial and gravitational constraints in young adults (Gaveau and Papaxanthis 2011;Vu et al 2016a). There are pieces of evidence suggesting that aging alters motor planning (Kanekar and Aruin 2014;Kubicki et al 2016;Casamento-Moran et al 2017;Wunsch et al 2017;Stöckel et al 2017), and that altered motor planning may cause falls (Lord and Fitzpatrick 2001;Lyon and Day 2005;Robinovitch et al 2013;Tisserand et al 2016). Since fall is inherently linked to gravity, understanding how older adults adapt their motor planning to gravity is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, inconsistent findings exist regarding when skills are adult‐like in nature (Wunsch et al, ). Observing the other end of the developmental lifespan, three recent studies exploring changes with aging highlight negative developmental trends, such that a decrease in the end‐state comfort effect is attributed to cognitive decline (Scharoun, Gonzalez, Roy, Bryden, ; Stöckel, Wunsch, & Hughes, ; Wunsch, Weigelt, & Stöckel, ).…”
Section: Introductionmentioning
confidence: 99%
“…This ability to plan for ESC, although present at an early age (Stöckel & Hughes, 2016;Weigelt & Schack, 2010), has been shown to develop into late childhood (Wilmut & Byrne, 2014b). Recent studies demonstrate a growing interest surrounding the development of motor planning at the other end of the lifespan (Niermeyer, Suchy, & Ziemnik, 2017;Scharoun, Gonzalez, Roy, & Bryden, 2016, 2017Stöckel, Wunsch, & Hughes, 2017;Wunsch, Weigelt, & Stöckel, 2017) and have highlighted a negative developmental trend for ESC planning in late adulthood (Scharoun et al, 2016(Scharoun et al, , 2017Stöckel et al, 2017;Wunsch et al, 2017).…”
mentioning
confidence: 99%
“…However, in conditions where an actual grasping of an upturned glass was allowed, older adults' grasp selection for ESC did not differ from young adults. In another thread of research, Stöckel et al (2017) and Wunsch et al (2017) used a bar transport task, which mimics the upturned glass analogy, and considered both a unimanual and a bimanual condition. The number of grasps resulting in ESC was significantly lower in an older-old group (71-86 years) compared to young adults (19-28 years) and a younger-old group (60-70 years), particularly when the task was more demanding and bimanual movements were required.…”
mentioning
confidence: 99%